Integrated Mobile and Web-based Application for Enhancing Delivery of HIV/AIDS Healthcare Information in Tanzania - Mwammenywa, Ibrahim A.; Nkotagu, Michael H.; Kaijage, Shubi F. (Tanzania Journal of Engineering and Technology, 2020)
This study aims to develop an integrated e-health platform for enhancing delivery of HIV/AIDS healthcare information in Tanzania, which consists of a mobile application and a web-based system. The study is based on the system's functional and non-functional requirements for an e-health system for delivery of HIV/AIDS healthcare information. The Rapid Application Development (RAD) model was adopted during the system development. The system requirements were modelled into Data Flow Diagram (DFD) in order to obtain the clear flow of the HIV/AIDS healthcare information between the clients and HIV/AIDS healthcare practitioners. With the use of different software development tools and environment such as Android studio and Symfony framework; both android application and web-based system were developed. Finally, the developed system was tested for individual module functioning as well as the functioning of the fully integrated system. The user acceptance survey gave the mean score of above 4 on the scale of 5 for each tested aspect of the system. These scores show that the developed system was positively accepted by the users and commended the Ministry of Health and to deploy the system for enhanced delivery of HIV/AIDS healthcare information. Keywords: Electronic Health (e-health), HIV/AIDS Healthcare Information, Mobile Application, Mobile Health (m-Health), Web-based System.